Upaya Penangan Diare dengan Bubur Tempe pada Balita di Desa Sambirejo - Ersa Kusuma Wardhani; Tri Hastuti; Trias Jayantina; Tyas Dwi Rahayu; Wahyu Ditya Nugraha (STIKes Ibnu Sina Ajibarang, 2024)
Diarrhea is still a health problem, especially in children. According to the World Health Organization (WHO, 2017) diarrhea is the occurrence of defecation with a consistency that is more liquid than usual, with a frequency of 3 times or more in a 24 hour period. Diarrhea is an environmental-based disease caused by infection with microorganisms including bacteria, viruses, parasites, protozoa, and is transmitted via fecal-oral route. Diarrhea is the second cause of death among children under five in the world. Nearly 1 in 5 child deaths, around 1.5 million each year, are due to diarrhea. Diarrhea is the cause of 40% of under-five deaths throughout the world every year. The results of interviews with mothers who have children under five in the Sambirejo area showed that the majority did not know about treating diarrhea in toddlers with tempeh porridge. Objective: to provide understanding to the public that tempeh porridge can treat diarrhea in toddlers. Method : applied in community service is socialization and health education regarding diarrhea and its management by providing tempe porridge. Community service activities were carried out on Thursday 19 October 2023 at residents' homes in Sambirejo Village. The community service activity was attended by approximately 20 people. Results : Observations from this health education activity showed that the majority of participants were active in asking questions and answering questions given by the community service team and were able to demonstrate again how to make tempeh porridge. Providing health education about treating diarrhea by providing tempe porridge has proven that the community's knowledge and skills increase after being given the education.